Defects And Destruction On Roads With Cement Concrete Pavements - Tuxtayev Matchon Bekchonovich; Mamatkulov Muzaffar Tashbayevich; Axrarov Abrorbek Muxammadaliyevich (Genius Journals, 2022)
The article analyzes various types of defects on cement concrete pavements, gives recommendations for their elimination during operation.
Keywords: Cement concrete; residual deformations; cracks; defects